Text Review using data mining Classification Technique - พรมน้ำอ่าง ประพัฒน์; พงศ์ขจร วสุวรรธน์; จิระวิชิตชัย นิเวศ (Progress in Applied Science and Technology, 2016)
Recently, technology plays a lot of role in daily life and has plenty text review on the web which is used to specify the interesting points in the product selling in the website. This mention method helps the purchaser able to read the text review of the product before deciding to make the purchase order which makes high advantage in proposing selling products on the website. These articles presents the Movie Text Review using data mining classification technique consists of SVM, Decision Tree, K-NN and Naïve Bayes techniques. From the experiment, found that by using the SVM technique makes the highest accurate value of 86.26%.